Black phosphorus quantum dots: Nonlinear optical modulation material with ultraviolet saturable absorption - Wei, Hao; Fan, Wenxuan; Dong, Yulan; Wang, Yiduo; Zhou, Li; Wang, Yingwei; He, Jun (Frontiers in Physics, 2022)
Black phosphorus has attracted great interest for optical modulation and optoelectronic devices because of its ultrathin layer structure, tunable band gap, and high in-plane anisotropy. Especially in the near-infrared and mid-infrared bands, proof-of-concept applications, including saturable absorber resonators, photodetectors, and optical modulators based on 2D black phosphorus nanosheets, have been reported one after another. However, relatively few studies about black phosphorus have been reported in the ultraviolet band. Moreover, the poor stability of black phosphorus also has limited its development in practical applications. Here, we successfully prepared ultra-small black phosphorus quantum dots (BPQDs) with an average thickness of 2.0 ± 0.4 nm and a diameter of 2.2 ± 0.6 nm. Further, we have also fabricated BPQDs-Ormosil gel glasses. Through an open-aperture Z-scan experiment, BPQDs-Ormosil gel glasses demonstrated excellent nonlinear optical modulation in the ultraviolet band, which proposes a new idea for the ultraviolet optical modulation elements such as saturable absorption devices.